2013
DOI: 10.1007/s10803-013-1765-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Socialization for High School Students with ASD by Using Their Preferred Interests

Abstract: There has been a paucity of research on effective social interventions for adolescents with ASD in inclusive high school settings. The literature, however, suggests that incorporating the student with ASD’s special interests into activities may help improve their socialization with typical peers. Within the context of a multiple baseline across participants design, we implemented lunchtime activities incorporating the adolescent with ASD’s preferred interests that were similar to ongoing activities already ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 42 publications
1
80
0
1
Order By: Relevance
“…Koegel, et. al., 2012; Koegel, et al, 2013) as follows: (a) The student with ASD’s percent intervals with engagement with their typical peers; and (b) The student with ASD’s rate of initiations made to their typical peers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koegel, et. al., 2012; Koegel, et al, 2013) as follows: (a) The student with ASD’s percent intervals with engagement with their typical peers; and (b) The student with ASD’s rate of initiations made to their typical peers.…”
Section: Methodsmentioning
confidence: 99%
“…One intervention discussed in the literature is the incorporation of the preferred interests of students with ASD in the context of school clubs, wherein both the student with ASD and typical peers are able to contribute their respective strengths to social interactions (Koegel, Fredeen, Kim, Danial, Rubinstein, & Koegel, 2012; Koegel, Kim, Koegel, & Schwartzman, 2013; Koegel, Vernon, Koegel, Koegel, & Paullin, 2012). This type of social intervention provides a common ground upon which social relationships and friendships can be formed with typically-developing peers who share similar interests (Cohen, 1977; Feld, 1982).…”
mentioning
confidence: 99%
“…Despite the frequent psychosocial difficulties in this population, very few studies have focused on areas such as social conversation with adults, a skill that is essential for meaningful relationships (Gantman, Kapp, Orenski, & Laugeson, 2012;Howlin & Yates, 1999). The few studies that have targeted this population have shown general overall improvement in social functioning, after interventions that have focused on specific skills such as question-asking (Detar, 2013) as well as treatment in the context of peer groups (Gantman et al, 2012;Mesibov, 1984) and during inclusion with typical peers (R. Koegel, Kim, Koegel, & Schwartzman, 2013). This study also resulted in improvements in social conversation with positive generalized improvements for several participants in a variety of areas.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers observed Austin during free play and interviewed the classroom teacher, parents, and other school staff in order to determine which activities Austin most frequently engaged in (Koegel et al 2012a(Koegel et al , 2012b(Koegel et al , 2013. Austin exhibited repetitive behaviors that involved organizing, sorting, and lining up items by shape, size, or color.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous research, functional play was defined as using play materials in a manner appropriate to their intended function, for example, rolling a toy car along the ground (c.f., Lang et al 2009). Social engagement was defined based on the description provided by Koegel et al (2013) as the child with ASD remaining in proximity (i.e., 1.5 m) to the peer and appropriate engagement in one of the following social activities with the peer: playing a game (e.g., Connect Four®), creating something together (e.g., building a block tower), or oriented toward the peer while observing the peer's play (e.g., watching the peer take a turn during a game).…”
Section: Methodsmentioning
confidence: 99%